The Right to Buyback in Murabahah Akad with the Ba'i al-Wafa' System Based on Maqashid Sharia - Dyah Ochtorina Susanti; Rahmadi Indra Tektona; Siti Nur Shoimah (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2022)
The objective of this article is to find out whether the right to buy back under a murÄbaá¸¥ah akad with the bay’ al-wafÄ’ system is contrary to maqÄá¹£id al-sharÄ«a or not. MurÄbaá¸¥ah akad with the bay’ al-wafÄ’ system is a new type of contract resulting from modification. Applying akad optimally must contain benefits for the community by referring to the maqÄá¹£id al-sharÄ«a. This study uses a normative legal research method with a statute legal approach and a conceptual approach. This study resulted in the findings that the right to buy back in a murÄbaá¸¥ah akad with the bay’ al-wafÄ’ system is not contrary to maqÄá¹£id sharia because it provides benefits, profits, pleasure, benefit, and happiness for the parties (seller and buyer). MurÄbaá¸¥ah akad with the bay’ al-wafÄ’ system also has fulfilled 5 (five) main elements of realizing benefit, i.e., maintaining religion because it can keep humans from riba; nourish the soul, because sellers who get funds quickly and buyers who make a profit can use them to sustain their lives; maintaining the reason because the seller uses his mind to sell his products to the buyer to get funds to meet his needs, and the buyer uses his mind in seeking lawful sustenance (earning a profit) through the use of this akad; maintaining offspring, because will provide blessings and benefits for children, grandchildren, and their offspring; maintaining the property, because someone who has more assets (buyer) can use his wealth to help other people who need funds.